Slums how informal real estate markets work - Birch, Eugenie L.; Chattaraj, Shahana; Wachter, Susan M. 1943- (University of Pennsylvania Press, 2016)
Large numbers of people in urbanizing regions in the developing world live and work in unplanned settlements that grow through incremental processes of squatting and self-building. Slums: How Informal Real Estate Markets Work shows that unauthorized settlements in rapidly growing cities are not divorced from market forces; rather, they must be understood as complex environments where state policies and market actors still do play a role. In this volume, contributors examine how the form and function of informal real estate markets are shaped by legal systems governing property rights, by national and local policy, and by historical and geographic particularities of specific neighborhoods. Their essays provide detailed portraits of individuals and community organizations, revealing in granular detail the working of informal real estate markets, and they review programs that have been implemented in unconventional settlements to provide lessons about the effectiveness and implementation challenges of different approaches.Chapters explore the relationships between informality, state policies, and market forces from a range of disciplinary perspectives and on different scales, from an analysis of the relationship between regulations and housing in 600 developing world cities to an ethnographic account of the buying and selling of houses in Rio de Janeiro's favelas. While many of the book's contributors focus on the emerging economies of India and Brazil, the conclusions drawn illustrate dynamics relevant to developing countries throughout the Global South. The diversity of perspectives combines to create a rich understanding of an important, complex, and understudied topic.Contributors: Arthur Acolin, Sai Balakrishnan, Eugenie L. Birch, José Brakarz, Shahana Chattaraj, Sebastian Galiani, David Gouverneur, Yvonne Mautner, Paavo Monkkonen, Vinit Mukhija, Janice E. Perlman, Lucas Ronconi, Bish Sanyal, Ernesto Schargrodsky, Patrí
Description based on online resource; title from PDF title page (publisher's Web site, viewed May 10, 2017)
Keywords: Gesellschaft; Real property -- Social aspects -- Brazil; Real property -- Social aspects -- India; Slums -- Social aspects -- Brazil; Slums -- Social aspects -- India; Immobilienmarkt; Slum; Brasilien; Indien; Aufsatzsammlung; Fallstudiensammlung